2020
DOI: 10.1186/s12866-020-01936-y
|View full text |Cite
|
Sign up to set email alerts
|

FocSge1 in Fusarium oxysporum f. sp. cubense race 1 is essential for full virulence

Abstract: Background: Fusarium wilt disease of banana is one of the most devastating diseases and was responsible for destroying banana plantations in the late nineteenth century. Fusarium oxysporum f. sp. cubense is the causative agent. Presently, both race 1 and 4 strains of Foc are creating havoc in the major banana-growing regions of the world. There is an urgent need to devise strategies to control this disease; that is possible only after a thorough understanding of the molecular basis of this disease. Results: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 34 publications
(41 reference statements)
0
10
0
Order By: Relevance
“…Mycotoxins are the main virulence molecules from F. graminearum , and their biosynthesis and regulation has been well studied ( Chen et al, 2019 ). In addition, secreted proteins were identified that modulate host plant defense and F. oxysporum virulence ( Chen et al, 2014 ; Liu et al, 2019 ; Ding et al, 2020 ; Gurdaswani et al, 2020 ). However, the molecular mechanism of F. oxysporum virulence toward tobacco plants remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mycotoxins are the main virulence molecules from F. graminearum , and their biosynthesis and regulation has been well studied ( Chen et al, 2019 ). In addition, secreted proteins were identified that modulate host plant defense and F. oxysporum virulence ( Chen et al, 2014 ; Liu et al, 2019 ; Ding et al, 2020 ; Gurdaswani et al, 2020 ). However, the molecular mechanism of F. oxysporum virulence toward tobacco plants remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown, that FocSge1 is required for the full virulence of F. oxysporum f. sp. cubense race 1 ( Gurdaswani et al, 2020 ) while FoRlm1 regulates anti-oxidant enzymes to control aerial hyphal growth, oxidative stress, cell wall biosynthesis, and virulence in F. oxysporum f. sp. cubense ( Ding et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Identi cation of potential target proteins of the pathogen is the foremost important step for assessing the interaction of protein with the ligand molecules through docking. Based on the literature survey and analysis, antifungal protein targets in Foc were identi ed as G protein ß subunit (FGB1) [22], Six Gene Expression 1 (SGE1) [23], RHO type GTPase (RHO1) [24], 5´ → 3´ Exoribonuclease 2 (XRN2) [25], C-24 sterol methyltransferase (ERG6), C-4 sterol methyl oxidase (ERG25) [26], Fusarium transcription factor 1 (FTF1), velvet [27], MADS-box transcription factor Rlm1 (Resistance to lethality of MKK1P386) [28], MAP kinase kinase 2 (Mkk2) [29], Secreted in Xylem 1 (SIX1), Secreted in xylem 6 (SIX6), Secreted in xylem 8 ( SIX8), Secreted in xylem 10 (SIX10) and Secreted in xylem (SIX13) [30]. Details on these protein targets of Fusarium oxysporum f. sp.…”
Section: Identi Cation Of Fungal Targetsmentioning
confidence: 99%
“…Velvet and Fusarium transcription factor 1 (ftf1) are two proteins that have been implicated in fungal proliferation, maturation and disease development with the earlier one having the role of regulating sexual and asexual development of the fungus [30]. SGE1 which is mainly regulating the expression of effector genes results in reduced pathogenicity of the organism [23]. Other transcription factor affected includes Rlm1 which is a MADS box transcription factor whose functional disruption can result in reduced aerial hyphal growth, virulence, increased susceptibility to oxidative stress, and reduced production of mycotoxins fusaric acid and beauvericin [28].…”
Section: Tri Oxystrobinmentioning
confidence: 99%
“…FA induces programmed cell death, increases ROS production and lipid peroxidation (Jiao et al, 2014;Singh and Upadhyay, 2014), alters electrolyte leakage, and reduces photosynthetic pigments (Wu et al, 2008a,b;Singh et al, 2017). FA is considered a virulence factor, since low levels of this mycotoxin are associated with a drop in vascular wilt severity (Ding et al, 2018;López-Díaz et al, 2018;Gurdaswani et al, 2020;Liu et al, 2020;Shao et al, 2020). Some of the symptoms caused by FA include leaf turgor and chlorophyll loss, vascular tissue browning, and necrosis (Wu et al, 2008b;Singh et al, 2017).…”
Section: Introductionmentioning
confidence: 99%